Primary mediastinal seminoma with azoospermia: case report and review of the literature - Li, Zhiwei; Zhu, Qiqi; Niu, Shaorui; Xiao, Kaibing; Xiao, Zhiyang; Yang, Pang (Frontiers in Oncology, 2024)
Introduction Since the first report, primary mediastinal seminoma has a low incidence in the population, and it mainly affects young and middle-aged men, is clinically rare, and accounts for a very small proportion of mediastinal tumors. In this study, we describe the first case of primary mediastinal seminoma with azoospermia and hypothesize that the coexistence of the two disorders may not be a coincidence. Case report A 16-year-old man presented with chest tightness and chest pain, a mediastinal mass on chest CT, and abnormal 18F-fluoro-deoxyglucose uptake on a PET-CT scan. By biopsy of the mass, the pathological diagnosis was a primary mediastinal seminoma. Because chemotherapy is included in the treatment of the tumor, the patient underwent sperm freezing before treatment, considering that chemotherapy can affect fertility, but the patient was diagnosed with azoospermia. Finally, the patient underwent tumor resection and postoperative chemotherapy. No tumor recurrence was observed at the current follow-up. Conclusion Primary mediastinal seminoma is mainly confirmed by histopathological examination, and surgery and chemoradiotherapy are the current treatments. In patients with mediastinal seminoma or azoospermia, doctors should be aware that the two disorders may coexist, especially in men who have fertility requirements or long-term infertility, and that examination of the mediastinum and semen may lead to unexpected findings in the diagnosis and treatment. For mediastinal germ cell tumors, genetic testing is of great value in the treatment of tumors and the prediction of associated diseases. Future studies exploring the potential correlation between mediastinal seminoma and azoospermia will be prospective.